The Use of Organizational Knowledge in the Process of Strategic Planning: An Example of a City Municipality - Bayraktar, Berat Bir; Kakırman Yıldız, Asiye (Information World, 2007)
The purpose of this study is to underline the importance of the concepts of organizational knowledge and strategic planning for organizations and to define the relationship between these concepts. A case study was carried out in an Istanbul municipality to demonstrate how the municipality administration made use of the organizational knowledge in strategic planning.